Somewhere along the way - Thomas, Jodi.; Copyright Paperback Collection (Library of Congress) (New York : Berkley Publishing Group, 2010)
When Reagan Truman's life is put in jeopardy, the whole town of Harmony, Texas, comes together to save her.
"A Harmony novel"--Cover.
Keywords: Texas -- Fiction; Love stories